PENGARUH KOMPETENSI, AKUNTABILITAS, TRANSPARANSI, DAN PARTISIPASI MASYARAKAT TERHADAP EFEKTIVITAS PENGELOLAAN ANGGARAN DANA DESA - Artika, Meylina; Fitriasuri, Fitriasuri; Alvia, Risa (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2023)
The competence of village officials in managing village fund budgets used for the benefit of the community has been misused for personal gain. This research provides a deeper understanding of the relationship between these factors and their impact on village fund budget management. In addition, proposing policy recommendations that can improve village fund budget management. The research method used was a quantitative method involving 113 respondents who were people from 19 villages in Muara Lakitan District. Sampling was performed using the slovin formula, and data analysis using multiple linear regression analysis through the SPSS application program version 26. This research shows that community competence and participation have a positive influence on the effectiveness of village fund budget management. Meanwhile, accountability and transparency do not have a significant effect on the effectiveness of village fund budget management. In addition, the results of this study have important relevance in the context of improving village fund management policies in the future.